Bauran Pemasaran Dan Pengaruh Perilaku Konsumen Dalam Membeli Produk AICE Di UD. Stan Jaya Kelurahan Paupire Kecamatan Ende Tengah Kabupaten Ende - Yenny Kila; Yosef Moan Banda (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
This study aims to determine: the marketing mix and the influence of consumer behavior in buying Aice products at UD. Stan Jaya. The research approach is quantitative descriptive. Data collection was carried out using observation, questionnaire and documentation techniques. Technical analysis of the data used kolmogrov-smirnov test, the test was carried out with the help of the SPSS 16.0 program for windows and hypothesis testing using the t test. While the samples in this study were Aice ice cream consumer of 50 people. The research findings show that marketing mix simultaneously influences consumer behavior. Partialy, product, price, promotion and location influence consumer behavior. Where the count ? r table is 1.758 ? 0.284 this means that there is a significant effect between the marketing mix with consumer behavior in buying Aice products. Location is the most dominant influence on consumer behavior.